The Chronology of Development Tracer Study System at Tanjungpura University - Kurniatuhadi, Rikhsan; Hadary, Ferry; Sulistyarini, Sulistyarini; Anzani, Yunita Magrima; Fahruna, Yulyanti; Muthahhari, Morthezza (Jurnal Teknologi Informasi dan Pendidikan, 2024)
The implementation of the Tracer Study at Tanjungpura University has been carried out since 2011 and became an electronic or online system in 2015. The system and design of the online tracer study at Tanjungpura University experienced dynamics that were adjusted to internal and external factors from 2015 to 2022. The influencing factors included changes in the mandate Dikti/Belmawa, resources, and the development of tracer study instruments. These factors cause several obstacles and challenges in creating an efficient Tracer Study system and desain. The purpose of As discussion is to review an overview of the development of the Tracer Study system and design at the Tanjungpura University to create a more efficient Tracer Study system. The research method is carried out by identifying a system model developed from 2015 to 2022 with the Borg and Gall models. The search results show that there have been system and design changes four times from 2015 to 2022. Furthermore, some systems and designs are less efficient in implementing the tracer study from 2015 to 2019 by making an online surveyor input system to reduce the tracer study's essence and function. However, in 2020, the online filling process has all been directed by alumni to fill in directly.